The impact of the Covid-19 pandemic on the life of professionals working in public health in a municipality of Mato Grosso (Research, Society and Development, 2022)
The Covid-19 pandemic has turned the work environment into a place of imminent danger for health workers. Because they are on the front line of the disease, they face biological, psychological and physical risks. The objective of this work is to know the impact of the Covid-19 pandemic on the lives of health workers in a municipality in the interior of the state of Mato Grosso. This is an exploratory, descriptive and qualitative study, with interviews conducted in June/July 2021. The sample consisted of thirteen professionals working in public health in this municipality, five from Primary Care, four from the Emergency Operational Center (COE) and four from a Regional Hospital. They were selected by convenience criteria and a semi-structured questionnaire was used. Data analysis was performed based on thematic content analysis, proposed by Minayo, and four categories emerged from it. The results showed that health workers suffered a strong negative impact on their lives due to their work activity during the pandemic period, which was reflected in the work environment, family and social life, physical and emotional health and spirituality. Finally, it was noted that strategies to minimize these impacts are of paramount importance for this population.